Nitric oxide promotes energy metabolism and protects mitochondrial DNA in peaches during cold storage - Ren, Yuanyuan; Zhu, Shuhua (Frontiers in Plant Science, 2022)
Mitochondria are essential organelles related to energy metabolism and are susceptible to oxidative damage. In this experiment, peaches (Prunus persica) were treated with distilled water as the control, 15 μmol L-1 nitric oxide (NO), and 20 μmol L-1 carboxy-PTIO (NO scavenger), respectively. The changes in mitochondrial physiological indicators, energy metabolism process, mitochondrial DNA (mtDNA) damage and repair were quantified. Compared with the control, NO treatment reduced mitochondrial oxygen consumption and the reactive oxygen species content, increased mitochondrial respiration control rate, and promoted energy metabolism by influencing the activities of citrate synthase, aconitase, isocitrate dehydrogenase, and α‐ketoglutarate dehydrogenase in the tricarboxylic acid cycle and ATP synthase activity in peach mitochondria. NO treatment also maintained the relative copy number of mtDNA and the relative amplification of Long-PCR in peaches, decreased the level of 8-hydroxy-2 deoxyguanosine, and upregulated the expression of PpOGG1, PpAPE1, and PpLIG1. These results indicated that exogenous 15 μmol L‐1 NO treatment could reduce mtDNA oxidative damage, maintain mtDNA molecular integrity, and inhibit mtDNA copy number reduction by reducing the reactive oxygen species content, thereby promoting mitochondrial energy metabolism and prolonging the storage life of peaches at low temperatures.